Crack Propagation Behavior of a Ni-Based Single-Crystal Superalloy during In Situ SEM Tensile Test at 1000 °C - Wenxiang Jiang; Xiaoyi Ren; Jinghao Zhao; Jianli Zhou; Jinyao Ma; Wenjing Zhang; Yuefei Zhang; Ze Zhang (Crystals, 2020)
An in situ scanning electron microscope (SEM) tensile test for Ni-based single-crystal superalloy was carried out at 1000 °C. The stress displacement was obtained, and the yield strength and tensile strength of the superalloy were 699 MPa and 826 MPa, respectively. The crack propagation process, consisting of Model I crack and crystallographic shearing crack, was determined. More interestingly, the crack propagation path and rate affected by eutectics was directly observed and counted. Results show that the coalescence of the primary crack and second microcrack at the interface of a γ/γ′ matrix and eutectics would make the crack propagation rate increase from 0.3 μm/s to 0.4 μm/s. On the other hand, crack deflection decreased the rate to 0.05 μm/s. Moreover, movement of dislocations in front of the crack was also analyzed to explain the different crack propagation behavior in the superalloy.